DETERMINATION OF GERMINATION OF RYE SEEDS UNDER LABORATORY CONDITIONS - B.R. Hasanov (European Journal of Agricultural and Rural Education, 2024)
In this article, in the laboratory of "Plant Physiology and Biochemistry" of the Southern Research Institute of Agriculture, the laboratory germination of seeds, as well as the germination energy, the number and length of seeds of winter rye varieties, were determined and analyzed.